2011
DOI: 10.4321/s0004-05922011000300043
|View full text |Cite
|
Sign up to set email alerts
|

Estrutura populacional e variabilidade genética da raça caprina Marota

Abstract: A raça caprina Marota é parte do patrimônio genético do Brasil, formada por animais altamente adaptados ao semi-árido nordestino. Este estudo avaliou a estrutura genética do núcleo de conservação da raça Marota, mantida pela Embrapa Meio Norte. SUMMARYMarota breed goat is part of the Brazilian genetic patrimony, consisting by animals highly adapted to semi-arid region. This study evaluated genetic structure of Marota breed from Embrapa Meio Norte conservation nucleus. Pedigree records of 663 animals, which we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 6 publications
(9 reference statements)
2
10
0
6
Order By: Relevance
“…Thus, animals from another population should be introduced to increase the genetic base of the population. Barros et al (2011), evaluating the Brazilian goat breed Marota, found the effective number of founders and ancestors was 48 animals and the number of ancestors that explained 50 % of population variability was 22. In an analysis of four Canadian pig breeds, Melka and Schenkel (2010) determined the effective number of founders to be 275, 11, 56 and 54 for the Duroc, Hampshire, Lacombe and Landrace breeds, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, animals from another population should be introduced to increase the genetic base of the population. Barros et al (2011), evaluating the Brazilian goat breed Marota, found the effective number of founders and ancestors was 48 animals and the number of ancestors that explained 50 % of population variability was 22. In an analysis of four Canadian pig breeds, Melka and Schenkel (2010) determined the effective number of founders to be 275, 11, 56 and 54 for the Duroc, Hampshire, Lacombe and Landrace breeds, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…This result is expected in a small population, even when minimum coancestry mating is performed; if no action is taken, a further increase in inbreeding in later generations is expected. The individual AR can be used to choose animals for reproduction, such that animals with low AR should be preferred for long-term inbreeding control (Barros et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Entre os parâmetros populacionais analisados (Tabela I), verificou-se que o número efetivo de ancestrais (fa) encontrado foi de 29, valor semelhante ao numero efetivo de fundadores (fe). De acordo com Barros, et al (2011) Valores observados foram considerados baixos para fe e fa, quando comparados com o número de animais fundadores, levando o rebanho a se desenvolver através de uma base genética que apresenta estreita relação, o que pode resultar em perdas de genes de origem. Os valores de fe e fa observado no presente estudo foram inferiores aos encontrado por Oravcová (2013) em estudo com caprinos da raça White Shorthaired, e por Rashidi et al (2015) com caprinos da raça Markhoz.…”
Section: Resultsunclassified
“…Apesar da sua importância, ainda são poucos os estudos que visam avaliar a estrutura populacional, bem como os efeitos da endogamia sobre características sob seleção em caprinos. Destacam-se os trabalhos de, Barros, et al (2011) e Rashidi, et al (2015.…”
Section: Introductionunclassified
“…Valores do F IS observados nos animais adultos e nas crias, respectivamente, iguais a 0,086±0,001 e 0,042±0,003 (Tabela I), apesar de baixos, indicam que não convém considerar que a frequência de homozigotos na população está em equilíbrio em relação ao esperado para situação de acasalamento ao acaso. Porém, Barros et al (2011) avaliaram a estrutura genética desse rebanho utilizando dados de genealogia e não constataram existência de consanguinidade (F IS= -0,22), resultado que consideraram em desacordo com a estreita base genética encontrada no rebanho analisado.…”
Section: Manejo IIunclassified